2023
DOI: 10.1134/s1063780x2360010x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cold Atmospheric Plasma Jet when Excited by Sinusoidal and Positive Pulse Voltages for Medical Applications

Abstract: Low-temperature plasma jets at atmospheric pressure generated by sinusoidal and positive pulsed voltages interact differently with the treated surface. In the experiment and in numerical simulations, we compare the operating modes of helium plasma jets for these types of operating voltages. The discharge current on the treated surface over time and the surface heating are studied for different discharge parameters acceptable for anticancer therapy. The intensity of the emission spectrum is analyzed to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In our earlier study of CAPJ regimes we demonstrated that the intensity of CAPJ interaction with the target is a nonmonotonic function of the voltage amplitude and frequency [6,7,31]. The aim of this study is to find a CAPJ regime with optimal characteristics: (1) streamers touch the target at each voltage cycle, (2) the current amplitude near the target I has the maximum value and (3) the temperature in the contact zone is less than 42 • C. We expected that the maximal cytotoxic effect of CAPJ treatment depends on a regularity of streamer propagation to the target and increases with an increase of the discharge current on the treated surface.…”
Section: Capj Operation Modesmentioning
confidence: 95%
See 2 more Smart Citations
“…In our earlier study of CAPJ regimes we demonstrated that the intensity of CAPJ interaction with the target is a nonmonotonic function of the voltage amplitude and frequency [6,7,31]. The aim of this study is to find a CAPJ regime with optimal characteristics: (1) streamers touch the target at each voltage cycle, (2) the current amplitude near the target I has the maximum value and (3) the temperature in the contact zone is less than 42 • C. We expected that the maximal cytotoxic effect of CAPJ treatment depends on a regularity of streamer propagation to the target and increases with an increase of the discharge current on the treated surface.…”
Section: Capj Operation Modesmentioning
confidence: 95%
“…The bio experiments confirmed that the sin CAPJ with U = 3.3-3.5 kV and f U = 50 kHz is the most effective for suppression of cancer cells growth. Figure 5 from our paper [7] shows the measured current near the target, the applied voltage, and the viability of A549 cells after exposure to the sin CAPJ, at U = 3.5 kV, f U = 13 kHz and f U = 50 kHz. It should be noted that this effective sin CAPJ mode is difficult to maintain in the experiment.…”
Section: Capj Ignited With Sinusoidal Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…The plasma jet is defined by discharge propagation along that tube and subsequently in free space and contact with surfaces. A review paper (Corbella, et al 2023) and another review article (Schweigert, et al 2023) have been written to provide the current state-of-the-art in creating CAPJs.…”
Section: -The Plasma Jetmentioning
confidence: 99%